Deep eutectic solvent promoted tunable synthesis of nitrogen-doped nanoporous carbons from enzymatic hydrolysis lignin for supercapacitors. (March 2020) - Chen, Ling; Deng, Junqian; Song, Yandan; Hong, Shu; Lian, Hailan
Graphical abstract: Highlights: Dual functional eutectic mixture was applied for one-step synthesis of NPCs. Porosity and surface functionality of the NPCs were precisely tailored by urea. The unique carbons obtained are highly desirable for supercapacitors. Abstract: Dual functional deep eutectic solvent (DES) generated by the complexation of choline chloride and ZnCl2 was applied as both soft template and nitrogen source for the preparation of nanoporous carbons from sustainable lignin resource. Urea was purposely introduced as an additional nitrogen source as well as porogen. The diverse carbons were obtained by thermal treatment of the physical mixtures under N2 atmosphere in one-step. Physico-chemical characterization of the resultant carbons demonstrated that the presence of urea plays a key role in the formation of abundant micropores. With the incorporation of urea into the DES-templated system, the pore structure dominated by small mesopores evolved to a desirable micro-mesoporous hierarchical texture and exhibited a broccoli-like morphology. It has been demonstrated that the broccoli-like carbons exhibit enhanced electrochemical performance when used as electrodes in supercapacitors ascribed to the synergistic effect between rational micro-mesoporous structure and excellent nitrogen-doping efficiency ( ca . 4–10 wt%).